Seroprevalence of Brucellosis in dairy animals and their owners in selected sites, Central Highlands of Ethiopia - Temesgen Kassa Getahun; Beksisa Urge; Gezahegn Mamo (The International Journal of Tropical Veterinary and Biomedical Research, 2022)
A cross-sectional study was conducted from December, 2019 to May, 2020 with the aim of determining seroprevalence and identifying the potential risk factors of brucellosis in dairy cows with recent cases of abortion and their owners and farm workers in selected sites in the central highland of Oromia, Ethiopia. The overall seroprevalence of bovine and human brucellosis was 0.61% (95%CI: 0.016–2.09) and 1.21% (95%CI: 0.032–4.27) using combined RBPT and CFT tests, respectively. The late stage of abortion (OR = 14.74, p =0.0002), retained fetal membrane (OR = 32.74, p=0.006), market-based stock replacement (OR = 16.55, p=0.002), and presence of parturition pen (OR = 11.511, p=0.027) were found to be significantly associated with seropositivity for Brucella infection in dairy cattle. Human housing (OR = 1.8, p = 0.002), contact with aborted fetus (OR = 21.19, p = 0.017), and drinking raw milk from aborted (OR = 5.72, 0.019) and retained fetal membrane (OR = 4.22, p= 0.029) cows all had a significant influence on human brucellosis seropositivity. A structured interview question was administered to 284 respondents. Accordingly, most respondents had no knowledge of bovine brucellosis and their zoonotic effects (93.3%) in contrast most of them drink raw milk. Implementation of a test and slaughter strategy with compensation is recommended with this low prevalence. In the case of human brucellosis, implementing one health approach framework should be practiced.